2009
DOI: 10.1073/pnas.0904239106
|View full text |Cite
|
Sign up to set email alerts
|

Neural transplants in patients with Huntington's disease undergo disease-like neuronal degeneration

Abstract: The clinical evaluation of neural transplantation as a potential treatment for Huntington's disease (HD) was initiated in an attempt to replace lost neurons and improve patient outcomes. Two of 3 patients with HD reported here, who underwent neural transplantation containing striatal anlagen in the striatum a decade earlier, have demonstrated marginal and transient clinical benefits. Their brains were evaluated immunohistochemically and with electron microscopy for markers of projection neurons and interneuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
182
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 56 publications
(97 reference statements)
4
182
1
1
Order By: Relevance
“…Yet medial ganglionic eminence components are also important for both the proper development of striatal structures, and for their functional integration [25]. This may explain, at least in part, the lack of functional integration in the clinical trial reported by Hauser et al [13], in which the grafts only consisted of the most lateral part of the lateral ganglionic eminence [13,26].…”
mentioning
confidence: 99%
“…Yet medial ganglionic eminence components are also important for both the proper development of striatal structures, and for their functional integration [25]. This may explain, at least in part, the lack of functional integration in the clinical trial reported by Hauser et al [13], in which the grafts only consisted of the most lateral part of the lateral ganglionic eminence [13,26].…”
mentioning
confidence: 99%
“…However, an immune reaction has been observed at least in some cases. Recent studies have shown either the presence of anti-HLAs or inflammation [22,[105][106][107]. Krystkowiak et al [107] reported that as many as half of the HD patients had immunization develop against donor antigens during their phase II multi-center study of fetal neural transplants, with 1 patient showing full clinical, radiological, and biological symptoms of immune rejection.…”
Section: Immunogenicity Of Striatal Neural Graftsmentioning
confidence: 99%
“…This function is highly dependent on the integrity of striatal neural networks, in particular the fronto-striatal circuitry [19,20]. In the few transplanted patients autopsied, histological analyses at 18 months [21] to 10 years [9,22] after transplantation have provided both qualitative and quantitative measurement of cellular biology outcome of therapeutic fetal grafts. Human fetal grafts in these patients are rather small, representing no more than~4% of the corpus striatum volume and contain less than 60% of P-zones (i.e., region selectively positive for striatal interneurons or for striatal projection neurons markers [22].…”
Section: Supplying Graft For Hd Cell Therapy: the Devil Is In The Logmentioning
confidence: 99%
See 2 more Smart Citations